Thermal Requirements and Productivity of Squash (Cucurbita moschata Duch.) in the Cerrado-Amazon Transition - Souza, Adilson Pacheco de; Silva, Andréa Carvalho da; Pizzatto, Mariana; Souza, Manoel Euzébio de (Agrociencia Uruguay, 2017)
The thermal requirements for the phenological stages of squash cv. ‘Menina Brasileira Precoce’ were evaluated. The experiment was conducted in a Red-Yellow Dystrophic Oxil soil and Tropical Climate (Aw), with six winter/spring planting dates (June 5, 15, 25 and July 5, 15 and 25, 2013). The determination of accumulated degree days (GDD) was given considering the minimum and maximum basal temperatures of 12 and 35 °C. The average duration of phenological stages were 6.4, 29.2, 48.2, 60.9, 63.0 and 69.6 days, with demands for thermal time of 88.2; 401.9; 661.5; 832.5; 858.6 and 985.5 GDD for phases to emergence, emission of first male button and first female button, first male flower and first female flower and early harvest. The proportion of female/male flowers ranged from 1:8.4 to 1:18.1. The smaller proportions of female/male flower provided a lower number of fruits per plant and productivity. The timing of fruit harvest should be set when fruit development reaches 100 GDD (8.0 days after the female flower emission).